Retos y oportunidades que ofrece la ampliación del Canal de Panamá para el Puerto de Cartagena (2016)
This article aims to analyze the challenges and opportunities of expanding the Panama Canal to the port of Cartagena, because this city is in a strategic point of the continent and its proximity to Panama means mobility and maximization of goods and ships through the canal expansion. This documentary and exploratory scope research was conducted using the logical - deductive analysis obtaining as main results are the opportunities and benefits in port, labor, commercial international matters, among others; that the challenges, which are mainly logistical and technological infrastructure, against which the Port of Cartagena is very well prepared.